Fieldnotes in the critical study of religion: revisiting Classical theorists - Newton, Richard; Touna, Vaia (Critiquing Religion: Discourse, Culture, Power, 2023)
This book introduces students to the so-called classics of the field from the 19th and 20th centuries, whilst challenging readers to apply a critical lens. Instead of representing scholars and their works as virtually timeless, each contributor provides sufficient background on the classic work in question so that readers not only understand its novelty and place in its own time, but are able to arrive at a critical understanding of whether its approach to studying religion continues to be useful to them today. Scholars discussed include Muller, Durkheim, Freud and Eliade. Fieldnotes in the Critical Study of Religion: Revisiting Classical Theorists therefore offers a novel way into writing both a history and ethnography of the discipline, helping readers to see how it has changed and inviting them to consider whatif anythingendures and thereby unites these diverse authors into a common field